2013
DOI: 10.1002/jgra.50252
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting daytime equatorial plasma bubbles observed by the C/NOFS satellite

Abstract: [1] We report the first observations of long-lasting daytime equatorial plasma bubbles with the Communication/Navigation Outage Forecasting System (C/NOFS) satellite. The most unusual features of the plasma bubbles are the persistence from the post-midnight sector through the afternoon sector and the extremely long lifetime of 12 h. In one case, the plasma bubbles were generated at 02:00-03:00 LT near the end of the main phase of a moderate magnetic storm and detected by C/NOFS over eight successive orbits, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 31 publications
(86 reference statements)
3
91
0
Order By: Relevance
“…As reported by Huang et al . [, ], the plasma bubbles detected by C/NOFS during one orbit may have moved to a later local time, ~2 h later, during the next orbit due to the corotation and the zonal drift. The plasma bubbles between 19:00 and 21:00 LT are most likely related to the PRE at 18:00–19:00 LT during the same orbit.…”
Section: Observationsmentioning
confidence: 99%
“…As reported by Huang et al . [, ], the plasma bubbles detected by C/NOFS during one orbit may have moved to a later local time, ~2 h later, during the next orbit due to the corotation and the zonal drift. The plasma bubbles between 19:00 and 21:00 LT are most likely related to the PRE at 18:00–19:00 LT during the same orbit.…”
Section: Observationsmentioning
confidence: 99%
“…Huang et al [2013] suggested that the zonal electric field associated with the disturbance dynamo or the overshielding electric field during magnetic storms was the possible driver. Huang et al [2013] suggested that the zonal electric field associated with the disturbance dynamo or the overshielding electric field during magnetic storms was the possible driver.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [2013] suggested that the zonal electric field associated with the disturbance dynamo or the overshielding electric field during magnetic storms was the possible driver. But Huang et al [2013] proposed that the high altitudes of plasma bubbles were the key factor for the long lifetime of the irregularities because the photoionization rate decreases rapidly with altitude, which could take a long time to fill the daytime bubbles. But Huang et al [2013] proposed that the high altitudes of plasma bubbles were the key factor for the long lifetime of the irregularities because the photoionization rate decreases rapidly with altitude, which could take a long time to fill the daytime bubbles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations